O Mestrado Profissional em Saúde da Família: análise dos (des)caminhos traçados nessa trajetória - Cardoso Júnior, Odemir Pires (2019)
Technological changes and current transformations in practically all Brazilian scenarios have demanded professionals with specialization profiles distinct from the traditional ones. The Professional Master in Family Health (MPSF) is an innovative modality of stricto sensu teaching, aimed at training leaders for transformative professional practice through the study of techniques, processes or themes through the incorporation of recognized scientific methodology, providing integration between the world of work and academia. Generally, the completion works produced in the Professional Masters courses are directed to the interpretation of the practice and the outline of action lines, but always addressing concepts, theories and discussion of ideas. This study aimed to analyze the productions and products of the Professional Master's Degree in Family Health - nucleader Federal University of Rio Grande do Norte (UFRN), defended from 2012 to 2016. This is a documentary, exploratory and descriptive study. qualitative approach. Data collection was performed in electronic databases (repository of dissertations and theses of the university; Lattes Platform; postgraduate program page) and through interviews. The data analyzed were: year of defense, title, author and advisor, work format (dissertation or other product / model), objectives, methodology used, line of research and themes, as well as area of professional practice and time of professional practice when of the defense of the dissertation. Similarly, we sought to analyze the technical and scientific productions developed and related to the Master, after its completion, as well as the activities and links of the graduates in this period until 2019. The final productions were measured in five concepts, each generating a quality indicator: quantity of approved completion work (PM) and quality of completed completion work produced. From this perspective, they were classified as Adequate to the research line [Very Good (MB) and Good (B)], or Need for improvement [Regular (R), Weak (F) or Insufficient (I)]. From this understanding, the data were complemented through content analysis from Bardin's perspective. The project was approved by the Research Ethics Committee of HUOLUFRN (Opinion No. 3,180,305 and CAAE No. 07046819.9.0000.5292). The following categories of analysis emerged: Master's degree as a SUS brand: one more reason to continue on the path of knowledge and Professional Profile, North and Choices: which master's degree we do and which master's degree we want? It is concluded that the criteria and items of institutional evaluation introduced by the Higher Education Personnel Improvement Coordination (CAPES) are known by the evaluated academic community, but need to be rethought to meet the specificities of the program.